Analisis Efektivitas Program Kencleng dalam Meningkatkan Kesadaran Berbagi Berbasis Nilai-Nilai Syariah - Ahmad Ridwan; Moh. Mukhsin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the effectiveness of the kencleng program in enhancing community awareness of charitable giving based on Islamic values. The research is motivated by the low consistency of participation in Islamic philanthropy, highlighting the need for simple and sustainable approaches to encourage habitual giving. Using a qualitative descriptive method, data were collected through in-depth interviews, observations, and documentation involving program participants. The findings show that the kencleng program effectively builds consistent giving habits through an accessible and flexible mechanism for small, routine contributions. The program also strengthens social interaction, trust, and spiritual motivation, as participants view charitable giving as both a social responsibility and an act of worship. The integration of behavioral approaches and religious values plays a key role in shaping sustainable sharing practices. The study concludes that accessibility, community involvement, and internalization of Islamic values are key factors influencing program success. These findings imply that similar community-based philanthropic models can be expanded to enhance social welfare and financial inclusion, particularly through digital integration and improved transparency.